Attempt to assess the results of the membership in the European Union and new integration policy challenges for Poland (Economic and Political Thought, 2015)
As the title suggests, the article aims to show the significance of Poland’saccession to the European Union for the Polish domestic and foreign policyfrom the perspective of its 11-year membership. However, it does not onlyaim to assess Poland’s membership so far but, first of all, show new threatsto the EU and – from this perspective – new challenges and tasks for theintegration policy of Poland. The main thesis of the article is a statementthat Poland’s accession to the EU was, and still is, one of the most importantevents in the modern history of Poland. It became a turning point in the Polishdomestic and foreign policy. Thanks to the accession to the EU, Poland hasstrengthened its position in Europe and the world. However, it must work outa new strategy today and determine further objectives for our activities in theEU, which should be adequate to the quickly changing international reality.